Հայոց ցեղասպանությունը և սիրիական սփյուռքի մամուլը - Արիսյան, Նորա («Զանգակ - 97»)
The paper deals with the reflections of Ihe Armenian Genocidc in the Syrian Arab Diaspora press. Taking into consideration that Ihe press is an importanl historical source, it is the first time that the Syrian press is studied and analyzed. The paper is based on 13 of the Syrian Diaspora newspapers published in Brazil, France etc. (1881-1921), which have dealt with the events of the Armenian massacres and genocide. Many of the articles speak about the Ottoman plan of the extermination of the non-Muslim minorities and about Ihe tortured Armenians after they were driven out of their lands. The study of the Syrian press leads to а conclusion that the Armenian genocide had a vast echo not only in the Syrian Arab press but also in the Syrian Arab Diaspora press, which testifies its nonpreservative attention toward the Armenian affairs.
Keywords: Մամուլ; Սփյուռք